The extract of zedoary-turmeric protects rats’ kidneys from damage caused by cisplatin - Intan, Putri Reno; Lienggonegoro, Lisa Andriani; Dany, Frans; Noviantari, Ariyani; Nikmah, Uly Alfi; Alegantina, Sukmayati; Rinendyaputri, Ratih; Isnawat, Ani; Sunarno, Sunarno; Fajarwat, Indah; Mariya, Sela Septima; Setiyono, Agus; et al. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The goal of this study was to examine how the combination of Curcuma zedoaria (zedoary) and Curcuma longa (turmeric) affected things on the kidneys of rats with acute kidney injury (AKI) from cisplatin by assessing the reduction of levels of cysteine-aspartic acid protease 3 (Caspase-3), kidney injury molecule-1 (KIM-1), and tumor necrosis factor-alpha (TNF-α) in renal tissue. Materials and Methods: There were five groups of rats: a normal control group, a cisplatin control group (CP), and three extract treatment groups (Ext100, Ext200, and Ext400). The CP group got cisplatin on day seven to cause AKI, while the extract group got cisplatin on day seven and the combined extract on days one through nine. On the 10th day, we looked at body weight, kidney weight, histology, and gene expression of KIM-1, TNF-α, and Caspase-3 by quantitative real-time polymerase chain reaction. We used SPSS (version 29.0) to do the statistical analyses. We present the data as mean ± SD or SEM and use analysis of variance and Tukey’s post-hoc test to analyze them. Results: Body weight decreased in the CP group, while it initially decreased and then increased in the extract groups, with Ext200 showing the greatest increase. Histologically, the CP group exhibited severe kidney damage, whereas the Ext200 group showed reduced damage. Gene expression of Caspase-3, KIM-1, and TNF-α was much lower in the Ext100 and Ext200 groups than in the CP group. Conclusion: Cisplatin-induced AKI caused less damage to the kidneys and less production of KIM1, TNF-α, and Caspase-3, suggesting that a 200 mg/kg combined extract of Zedoary and Turmeric could be used to prevent or lessen kidney damage. These results show that the extract could preserve the kidneys, which could lead to the creation of other treatments for those who are receiving cisplatin. J. Adv. Vet. Anim. Res., 12(3): 881–889, September 2025 http://doi.org/10.5455/javar.2025.l950